2020
DOI: 10.1002/jts.22613
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Sensitivity Prospectively Predicts Increased Acute Posttraumatic Stress and Related Symptoms After Sexual Assault

Abstract: Anxiety sensitivity is a potential risk factor for posttraumatic stress symptoms (PTSS) and has been hypothesized to contribute to PTSS development. However, few prospective studies have evaluated whether anxiety sensitivity predicts PTSS. In a subsample of 48 women sexual assault survivors enrolled as part of a larger prospective observational study, elevated anxiety sensitivity measured via a brief assessment 1 week after experiencing a sexual assault was concurrently associated with PTSS at 1 week and prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…The influence of AS on PTSS is of great concern regarding university students [25,26]. Previous studies revealed that AS is a significant factor associated with PTSS [27,28], and there are positive relationships between AS and posttraumatic stress disorder (PTSD) severity in military veterans [29], victims of domestic violence [30], and the general population [31]. Elevated trait AS was positively correlated with worry and fear of epidemic outbreaks during the Zika virus and Ebola virus epidemics [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of AS on PTSS is of great concern regarding university students [25,26]. Previous studies revealed that AS is a significant factor associated with PTSS [27,28], and there are positive relationships between AS and posttraumatic stress disorder (PTSD) severity in military veterans [29], victims of domestic violence [30], and the general population [31]. Elevated trait AS was positively correlated with worry and fear of epidemic outbreaks during the Zika virus and Ebola virus epidemics [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…This fits within prior research finding AS cognitive concerns are associated with increased cannabis withdrawal symptoms, 22 cannabis use in response to cravings, 23 and perceived barriers for quitting cannabis use, 24 but extend these associations to coping‐oriented cannabis use. AS cognitive concerns have been linked to a number of poor outcomes relevant to trauma‐exposed individuals, including increased PTSS 14 and insomnia, 16 suggesting it may be a particularly important facet of AS to assess and intervene upon in this population. This finding may be somewhat surprising since individuals with fears of cognitive dyscontrol could plausibly evaluate sensations associated with cannabis intoxication, such as trouble concentrating or derealization, as threatening.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety sensitivity (AS) is defined as the fear of sensations associated with anxious arousal, 12,13 sometimes termed the "fear of fear." AS is a transdiagnostic, cognitive-affective risk factor for both PTSS, 14 and substance use, 15 among other psychiatric conditions. 16 AS comprises three lower-order facets: physical concerns (e.g., elevated heart rate is interpreted as, "I am going to have a heart attack"), cognitive concerns (e.g., mental confusion is perceived as, "I am losing my mind"), and social concerns (e.g., blushing is believed to cause others to "judge me negatively").…”
Section: Introductionmentioning
confidence: 99%
“…AS, or the fear of anxious arousal, is hypothesized to promote the interpretation of typical posttraumatic reactions as threatening, thus motivating avoidance and maintaining a sense of threat (McHugh et al., 2017; Schmidt et al., 2019). Consistent with this hypothesis, AS has been shown to be elevated among individuals with PTSD (Taylor et al., 1992) and prospectively predicts PTSD symptom onset, severity, and course (Boffa et al., 2016; Short, Lechner, Bell, et al., 2020, 2022; Marshall et al., 2010). Indeed, our research team has found that higher levels of peritraumatic AS predict heightened PTSD, depression, and anxiety after sexual assault (Short, Lechner, Bell, et al., 2020).…”
mentioning
confidence: 88%
“…Consistent with this hypothesis, AS has been shown to be elevated among individuals with PTSD (Taylor et al., 1992) and prospectively predicts PTSD symptom onset, severity, and course (Boffa et al., 2016; Short, Lechner, Bell, et al., 2020, 2022; Marshall et al., 2010). Indeed, our research team has found that higher levels of peritraumatic AS predict heightened PTSD, depression, and anxiety after sexual assault (Short, Lechner, Bell, et al., 2020).…”
mentioning
confidence: 88%